Anti-Atherosclerosis Effect of Soy Milk in Rats Fed an Atherogenic Diet - Fauzan Azima (Cardiovascular and Cardiometabolic Journal, 2021)
Abstract: Atherosclerosis is a problem of cardiovascular disease. Consuming food containing excessive fat is a risk factor for atherosclerosis. Soy milk has been studied for its isoflavones which has antihyperlipidemic effect on the development of atherosclerosis. The aim of this study was to find out the effect of soy milk (Glycine max (L.) Merr.) administration on aortic’s histopathology profile (the length of wall thickness and number of foam cells) in male white rats (Rattus norvegicus) which were given the atherogenic diet that consists of goat’s fat and quail egg yolk. Material and Methods: A total of 30 rats were used in the true laboratory experiment which were distributed into 5 groups (n=6) using post-test only design, there were a normal diet group, an atherogenic diet group, an atherogenic and simvastatin 10 mg group, and another 2 groups that were given an atherogenic diet with soy milk doses variation of 12.5 g and 25 g respectively. Aortic’s histopathology was prepared with the paraffin method and stained with Hematoxylin-Eosin. Results: ANOVA test showed that soy milk variation dose were significantly (p<0.05) reduce the aortic wall thickness and foam cell. Conclusion: Providing soy milk with a certain dose is able to decrease the aortic’s wall thickness and foam cells in rats fed an atherogenic diet.